2017
DOI: 10.1371/journal.pone.0187435
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary research on flow rate and free surface of the accelerator driven subcritical system gravity-driven dense granular-flow target

Abstract: A spallation target is one of the three core parts of the accelerator driven subcritical system (ADS), which has already been investigated for decades. Recently, a gravity-driven Dense Granular-flow Target (DGT) is proposed, which consists of a cylindrical hopper and an internal coaxial cylindrical beam pipe. The research on the flow rate and free surface are important for the design of the target whether in Heavy Liquid Metal (HLM) targets or the DGT. In this paper, the relations of flow rate and the geometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…For this study the particles are identical with their parameters given by Y = 5 The parameter values selected give rise to results that are consistent other computational and experimental studies in the literature (see, e.g., [2,4,5,9,14,23,24,26,32,41,43]). The value chosen for the Young's modulus ensures that the particles are stiff enough to display a realistic granular behaviour, while keeping the integration time step δt at manageable values.…”
Section: A Numerical Methodssupporting
confidence: 83%
See 1 more Smart Citation
“…For this study the particles are identical with their parameters given by Y = 5 The parameter values selected give rise to results that are consistent other computational and experimental studies in the literature (see, e.g., [2,4,5,9,14,23,24,26,32,41,43]). The value chosen for the Young's modulus ensures that the particles are stiff enough to display a realistic granular behaviour, while keeping the integration time step δt at manageable values.…”
Section: A Numerical Methodssupporting
confidence: 83%
“…The discharge of a silo by gravity has been during years a favourite process to explore the dynamics of granular materials [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. These media consist of macroscopic particles interacting by frictional contact forces, giving rise to a plethora of novel behaviours studied by engineers and physicists alike [16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The consistency between the simulation and experimental results was estimated at 100% (Table 1). The characteristics of gamma at 6.13 MeV energy each were experimentally measured by bombarding 19 F and 16 O nuclei with 113 MeV protons [51,52]. The simulation results estimated the values of 6.13 MeV and 6.14 MeV for 16 O and 19 F, respectively.…”
Section: Validation Of a Monte Carlo Program For Hard X-ray Productio...mentioning
confidence: 99%
“…The detection of elements was achieved through gamma spectra resulting from the spallation of a target under neutron irradiation. The neutron beam production was accomplished through proton beam irradiation of the spallation target [19]. In another study, Chiera et al [20] measured the gamma rays produced by proton and neutron spallation of various targets for element detection purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Under the insert, a free surface forms during the discharging, which was studied in Li et al's work. [23] The simulations showed that the free surface has a steady shape which could be fitted to be a paraboloid. Recently, Wojcik et al performed a large scale experiment of hopper flow with inserts and found that the recommendations based on previous small scale studies are no longer a good solution in large scale tests.…”
Section: Introductionmentioning
confidence: 95%